2019
DOI: 10.1111/jav.02075
|View full text |Cite
|
Sign up to set email alerts
|

Egg investment in response to helper presence in cooperatively breeding Tibetan ground tits

Abstract: Life‐history theory predicts a trade‐off between current and future reproduction to maximize lifetime fitness. In cooperatively breeding species, where offspring care is shared between breeders and helpers, helper presence may influence the female breeders’ egg investment, and consequently, survival and future reproductive success. For example, female breeders may reduce egg investment in response to helper presence if this reduction is compensated by helpers during provisioning. Alternatively, female breeders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…'s (2017) analysis with the effect obtained here, we found no general tendency of load lightening at the egg stage in cooperative breeders (estimate = −0.1320, CI = [−0.2921, 0.0281]; p = 0.1061; Figure S7; details in Supporting Information section F). Moreover, three additional studies have recently reported no evidence of prenatal load lightening in other cooperative breeders (Cusick et al., 2018; Van de Loock, 2019; Zhao et al., 2019). The meta‐analysis on prenatal load lightening in cooperative breeders should therefore be revisited in a future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…'s (2017) analysis with the effect obtained here, we found no general tendency of load lightening at the egg stage in cooperative breeders (estimate = −0.1320, CI = [−0.2921, 0.0281]; p = 0.1061; Figure S7; details in Supporting Information section F). Moreover, three additional studies have recently reported no evidence of prenatal load lightening in other cooperative breeders (Cusick et al., 2018; Van de Loock, 2019; Zhao et al., 2019). The meta‐analysis on prenatal load lightening in cooperative breeders should therefore be revisited in a future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, additional evidence is available from previous studies. Clutch size and egg size (Zhao et al, 2019) as well as level of brood reduction (Lu et al, 2011) did not differ between helped and unhelped nests. Helped ground tit parents improved their survival largely because they adopted a “load‐lightening” strategy (Crick, 1992): reducing efforts of feeding young without compromising annual reproductive output (Lu et al, 2011).…”
Section: Discussionmentioning
confidence: 97%